Inovasi Editing Video CapCut Desktop di Media Creative Solutions (MCS) - Ramadan, M. Zidan; Ramadhan, Chandra; Abdullah, Fahmi (Ikatan Ahli Informatika Indonesia, 2025)
In today's digital era, video editing skills have become essential for professionals in the creative industry to enhance the competitiveness of digital content. This Community Service Program (PKM) aims to improve video editing skills using CapCut Desktop among staff and managers at Media Creative Solutions (MCS), Bandung. The program was conducted through an interactive training method that combined theory, demonstrations, and project-based simulations. The results showed significant improvements in participants' abilities to independently edit videos more professionally, as well as a better understanding of CapCut Desktop features. In conclusion, the practice-based training proved effective in enhancing participants' digital competencies, and it is recommended that similar training be conducted regularly to maintain and further develop their skills.